2011
DOI: 10.1002/jez.692
|View full text |Cite
|
Sign up to set email alerts
|

Degranulation of mast cells due to compound 48/80 induces concentration‐dependent intestinal contraction in rainbow trout (Oncorhynchus mykiss Walbaum) ex vivo

Abstract: Rainbow trout (Oncorhynchus mykiss) intestinal strips (n = 10) were mounted in an isolated organ bath and the effect of incremental doses of compound 48/80 was recorded. Compound 48/80 induced concentration-related contraction in all the examined strips following a sigmoidal dose-response curve fit. Values for maximal contraction (E(max) , g cm(-2)), negative logarithm of the EC(50) (pD(2)), and hill slope were, respectively (mean±standard error), 12.88 ± 0.51, 1.88 ± 0.05, 1.49 ± 0.27. The histological modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 82 publications
(100 reference statements)
2
36
0
Order By: Relevance
“…Both neutrophils and MCs have important role in intestine mucosal immunity and can co-occur in epithelium but most frequently in submucosal layer (Dezfuli et al, 2013(Dezfuli et al, , 2016, and the same finding was observed herein. MCs are present in many teleost species and are key regulatory cells active in coordination of many functions of the innate immunity (Dezfuli, Bo et al, 2015;Dezfuli et al, 2016;Secombes & Ellis, 2012 after inoculation of Aeromonas salmonicida exotoxins (Ellis, 1985;Vallejo & Ellis, 1989), although degranulation of MCs was induced ex vivo by use of compound 48/80 on intestinal tissue of rainbow trout (Manera, Giammarino, Borreca, Giari, & Dezfuli, 2011). In present survey, in L. saliens and L. ramada infected intestines, intense MCs degranulation was documented in close proximity to M. mugchelo plasmodia and its free mature spores.…”
Section: Transmission Electron Microscopymentioning
confidence: 48%
See 1 more Smart Citation
“…Both neutrophils and MCs have important role in intestine mucosal immunity and can co-occur in epithelium but most frequently in submucosal layer (Dezfuli et al, 2013(Dezfuli et al, , 2016, and the same finding was observed herein. MCs are present in many teleost species and are key regulatory cells active in coordination of many functions of the innate immunity (Dezfuli, Bo et al, 2015;Dezfuli et al, 2016;Secombes & Ellis, 2012 after inoculation of Aeromonas salmonicida exotoxins (Ellis, 1985;Vallejo & Ellis, 1989), although degranulation of MCs was induced ex vivo by use of compound 48/80 on intestinal tissue of rainbow trout (Manera, Giammarino, Borreca, Giari, & Dezfuli, 2011). In present survey, in L. saliens and L. ramada infected intestines, intense MCs degranulation was documented in close proximity to M. mugchelo plasmodia and its free mature spores.…”
Section: Transmission Electron Microscopymentioning
confidence: 48%
“…Records on contents of granules of fish MCs revealed that they have a panel of inflammatory mediators (Da Silva et al., ; Dezfuli, Lui, Giovinazzo, Boldrini, & Giari, ; Galindo‐Villegas et al., ; Silphaduang & Noga, ). MCs degranulation was observed after inoculation of Aeromonas salmonicida exotoxins (Ellis, ; Vallejo & Ellis, ), although degranulation of MCs was induced ex vivo by use of compound 48/80 on intestinal tissue of rainbow trout (Manera, Giammarino, Borreca, Giari, & Dezfuli, ). In present survey, in L. saliens and L. ramada infected intestines, intense MCs degranulation was documented in close proximity to M. mugchelo plasmodia and its free mature spores.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have demonstrated how MCs degranulate in response to exposure to a variety of known degranulating agents (Powell, Wright & Burka 1991;Manera et al 2011) and pathogens (Vallejo & Ellis 1989;Dezfuli et al 2008Dezfuli et al , 2013bpresent study) with the release of their contents. Mast cell products are pivotal in mediating leukocyte recruitment into inflammatory sites (Prykhozhi & Berman 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Several investigations have demonstrated how MCs degranulate in response to exposure to a variety of known degranulating agents (Powell, Wright & Burka ; Manera et al . ) and pathogens (Vallejo & Ellis ; Dezfuli et al . , ; present study) with the release of their contents.…”
Section: Discussionmentioning
confidence: 99%
“…In perciform fish, it has been reported that the mast cells contain histamine, which can regulate the fish’s inflammatory responses [42]. Moreover, MCs degranulation has been shown to promote intestinal contraction in Sparus aurata L. and in Oncorhynchus mykiss (Walbaum) [42,43]. …”
Section: Discussionmentioning
confidence: 99%